Supply of nutrients and productive responses in dairy cows given diets based on restrictively fermented silage - P. HUHTANEN (Agricultural and Food Science, 2008)
The objective of this paper is to review research which has evaluated the feeding of dairy cows with diets containing large proportions of grass silage. In Finland, milk production systems evolved are based on the use of restrictively fermented silages. Higher potential yields, smaller production risks than with cereal grains, short grazing period and high digestibility of grasses grown in northern latitudes have facilitated this development. Factors affecting nutrient supply from these diets are discussed. Digestibility is determined mainly by the stage of maturity at harvesting and it is not markedly affected by the level of energy and protein supplementation. Intake of grass silage is influenced both by digestibility and fermentation characteristics. Efficiency of microbial synthesis is high in animals given diets based on restrictively fermented silage but rumen fermentation pattern is characterised by low molar proportions of propionate. Production responses to additional concentrate are relatively small, especially when the amount of concentrate exceeds 10 kg day-1. High substitution of silage dry matter (DM), negative associative effects on digestion and partitioning of energy towards body tissues account for small production responses. Protein supplementation has consistently increased milk protein yield but responses do not appear to be related to the level of milk production, silage crude protein content, amount of concentrate or stage of lactation. The new protein evaluation system provides an accurate prediction of protein yield with the typical Finnish dairy cow diets. The high slopes (ca. 0.5) between protein supply and milk protein yield within experiments suggest that protein supply is suboptimal and protein supplements are used with a high efficiency.;